2017
DOI: 10.1016/j.celrep.2017.09.063
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Oligo Library and Sequencing Approach Reveals an Insulation Mechanism Encoded within Bacterial σ 54 Promoters

Abstract: We use an oligonucleotide library of >10,000 variants to identify an insulation mechanism encoded within a subset of σ promoters. Insulation manifests itself as reduced protein expression for a downstream gene that is expressed by transcriptional readthrough. It is strongly associated with the presence of short CT-rich motifs (3-5 bp), positioned within 25 bp upstream of the Shine-Dalgarno (SD) motif of the silenced gene. We provide evidence that insulation is triggered by binding of the ribosome binding site … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…This would represent a very efficient system for insulating expression from an operon to prevent spurious gene expression, which might be particularly useful to preserve expression of "mobile" operons that are laterally transferred and inserted in different replicons. A similar phenomenon of insulation was previously reported at the E. coli glnK N promoter and thoroughly characterized (Levy et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…This would represent a very efficient system for insulating expression from an operon to prevent spurious gene expression, which might be particularly useful to preserve expression of "mobile" operons that are laterally transferred and inserted in different replicons. A similar phenomenon of insulation was previously reported at the E. coli glnK N promoter and thoroughly characterized (Levy et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…bEBPs are special hexameric ATPases that use ATP hydrolysis to remodel theRNAP–σ 54 complex [ 103 ]. In addition, it was shown that bEBP binding sites can isolate or filter readthrough transcription from upstream genes [ 13 , 104 ]. This property makes these sequences similar to eukaryotic insulators.…”
Section: Enhancer-like Mechanisms In Eubacteriamentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) based methods such as ChIP-chip and ChIP-seq make it possible to determine the genome-wide binding locations of individual transcription factors of interest. Massively parallel reporter assays (MPRAs) have made it possible to read out transcription factor binding position and occupancy in vivo with base-pair resolution, and provide a means for analyzing additional features such as “insulator” sequences [68]. In vitro methods based on protein-binding microarrays [9], SELEX [1012], MITOMI [1315], and binding assays performed in high-throughput sequencing flow cells [16, 17] have made it possible to measure transcription factor affinity to a broad array of possible binding sites and can also account for features such as flanking sequences [15, 18, 19].…”
Section: Introductionmentioning
confidence: 99%